(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
The English language was introduced in the formal education when the Philippines was colonized by the United States in the early 20th century. For more than a century now, the use of the English language has been criticized and even condemned, revised and debated yet it is sustained up until today. This study aimed to determine the language preferably used as the medium of instruction for technical-vocational courses and its relationship to students’ motivation and anxiety to learn. The descriptive-correlational method was applied utilizing both self-report and modified questionnaires adapted from Motivated Strategies for Learning Questionnaire (Pintrich, et. al, 1990) and Foreign Language Anxiety Scale (Horwitz, E. K., et. al, 1986). The respondents were 40 shop instructors and 174 college freshmen in various shop classes. The data were treated utilizing weighted mean, percentage, Pearson Product-Moment Coefficient and t-test for the correlation coefficient. Results revealed an insignificant relationship between shop instructors´ preferred medium of instruction and students´ observation on shop instructors´ preferred medium of instruction. However, there were significant relationships between shop instructors´ preferred medium of instruction and students´ motivation to learn and shop instructors´ preferred medium of instruction and students´ anxiety in learning. The study concludes that the preferred medium of instruction is mixed English-Cebuano since it fosters better comprehension during lecture and hands-on. Furthermore, the medium of instruction influenced students´ motivation and anxiety; enthusiasm and discomfort during shop classes were related to the language used by instructors. An English-Cebuano Instructional Enrichment Module for Technical-Vocational Courses is proposed to be implemented.